Referral in the poetry of Saleh Al-Jaafari - Lafta, Ashwaq Hashim; Dawood, Salah Kadhim (Al-Adab Journal, 2021)
Referral is one of the important links in the linguistics of the text and has an effective effect in linking the parts of the text to each other and in their consistency, The designation of the reference elements is given to a section of the words that does not have an independent connotation, but rather refers to an element or other elements mentioned in other parts of the discourse, so the condition for their existence is the text and it is based on the principle of similarity between what has been mentioned in one maqam and what is later mentioned in another maqam, Muhammad Khatabi believes that the local elements of whatever kind are not satisfied with themselves in terms of interpretation, It is necessary to return to what it refers to in order to interpret it.